2005
DOI: 10.2207/qjjws.23.186
|View full text |Cite
|
Sign up to set email alerts
|

Friction-Stir-Welded Lap Joint of Aluminum to Zinc-Coated Steel

Abstract: Table 1 Chemical composition of the aluminum base metal 1100H24 (mass %). retracted while the tool continued to turn.The surface for the observation of microstructure was etched by 3% Nital to reveal the steel microstructure and subsequently by 1% HF aqueous solution to reveal the aluminum microstructure.The microstructure was observed with an optical microscope and SEM (Scanning Electron Microscope) for closer observations. A peel test was employed to estimate the fracture load of the obtained joint. The sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 13 publications
3
35
0
Order By: Relevance
“…This clearly suggests that the heat and pressure generated by the FSSW process are sufficient to promote diffusion bonding between the aluminum and steel sheets. It has been previously shown that when friction stir spot welds are made in Al/St lap joints, the presence of lower melting point coating on the steel appears to promote higher joint strengths and increased bonded areas (Elrefaey et al (2005) and Miyawa et al (2008)). A key feature of the coating is that the formation of an iron oxide is inhibited, and thus mutual inter-diffusion is promoted which may also facilitate the formation of IMC (i.e.…”
Section: Macro and Microstructural Characterizationmentioning
confidence: 96%
See 2 more Smart Citations
“…This clearly suggests that the heat and pressure generated by the FSSW process are sufficient to promote diffusion bonding between the aluminum and steel sheets. It has been previously shown that when friction stir spot welds are made in Al/St lap joints, the presence of lower melting point coating on the steel appears to promote higher joint strengths and increased bonded areas (Elrefaey et al (2005) and Miyawa et al (2008)). A key feature of the coating is that the formation of an iron oxide is inhibited, and thus mutual inter-diffusion is promoted which may also facilitate the formation of IMC (i.e.…”
Section: Macro and Microstructural Characterizationmentioning
confidence: 96%
“…Zn coated) in the automotive body industries shows an increasing trend in the last two decades thanks to enhanced vehicle structure durability. It has been proposed that Zn acts as a ''lubricant'' during friction stir lap welding by diffusing into the aluminum sheet and suppressing the melting point of the stirred material so that larger areas can be bonded (Elrefaey et al (2005)). In a further study, Miyagawa et al (2008) noted that the FSW Al joints with Zn coated steel exhibited considerably higher fracture load as compared with those involving uncoated steel.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These works suggested the existence of the plated layer significantly improved their weldability. [8][9][10] The previous reports, however, did not mention the reason why the plate metals could improve the weldability and the behavior of the plated layers during FSW and FSSW operation.…”
Section: Introductionmentioning
confidence: 99%
“…12 Crack growth behavior at the joint interface during the shear test for the Al/Fe lap joint welded by "ϩ0.1 mm" condition. Two enlarged pictures show the Al/Fe interface "before" and "after" the first load drop.…”
mentioning
confidence: 99%